Fraude à execução pela insolvência do executado e o confronto entre as posições do exequente e do terceiro adquirente - Miranda Filho, Luiz Antonio Castro de (2017)
The purpose of this study is to analysis the application of the institute of the fraud committed against creditors during an execution suit, especially about the subjective element in case of sale or encumbrance provided in article 792, item IV, of the Civil Procedure Code of 2015 (CPC/15). From an historical approach in Brazilian legal system about the fraud committed against creditors during an execution suit, this study intends to demonstrate the evolution of the institute, specifically in relation to the application and aspects of the subjective element to the fraud committed against creditor’s characterization. Also, from a critical analysis of the current jurisprudential understandings related to this institute, especially the Superior Court with its precedent 375, and several articles from CPC/73 and CPC/15 about the fraud committed against creditors, it will be demonstrated that it is becoming more and more difficult to recognize this istitute, causing flagrant damage to creditor and, overall, to the effective development of the judicial function. It is in this context, and from the analysis of the Superior Court current jurisprudence about the cases that the fraud was recognized or rejected based on the recent positioning, that the fraud committed against creditors during an execution suit will be addressed, to achieve the more proportional solution in relation to debtor, creditor and third interested buyer’s right